Dystonic Dysarthria in Wilson Disease: Efficacy of Zolpidem - Poujois, Aurélia; Pernon, Michaela; Trocello, Jean-Marc; Woimant, France (Frontiers in Neurology, 2017)
Wilson disease is a rare genetic disorder characterized by copper overload in the liver and the brain. Neurological presentations are mainly related to the accumulation of copper in the basal ganglia, the brainstem and the cerebellum. Dysarthria is a frequent symptom, with dystonic, spastic or parkinsonian components and is usually resistant to medical or voice rehabilitation therapies. Here we report the case of a patient with Wilson disease diagnosed at the age of 12, who presented a severe and constant dysarthria from dystonic origin which was unresponsive to benzodiazepines and anticholinergic drugs. When she was 25-year-old, she tried zolpidem at bedtime for sleeping difficulties and reported a paradoxical effect of this drug on her voice. To confirm the effect of zolpidem on her dystonic dysarthria, we realized a full evaluation of her dysarthria at baseline without zolpidem and after four days of treatment by 10 mg twice a day. Lexical access was evaluated by the semantic fluency; dysarthria by the Intelligibility Score, the spontaneous speech and reading rates, the maximum phonation time on the sustained vowel [a] and by a perceptive evaluation. Two hours after the intake of zolpidem, improvement of all the parameters tested, with the exception of the maximum phonation time, was observed. Semantic fluency increased by 59%, the spontaneous speech rate by 88% and the reading rate by 76%. General dystonia remained unchanged and the tolerance of zolpidem was satisfactory. Since then, the patient takes zolpidem 5 mg five times a day, and four years later shows persistent improvement in oral communication and a good drug tolerance. In this single-case study, we showed that regular daytime intake of zolpidem could have a persisting effect on a complex dystonic dysarthria that was resistant to usual medical treatments.